VD_FINDINFO Jug / 2011 / 186 vom 8. September 2011 - VD Tribunal cantonal (2011)
ORDONNANCE DE CONDAMNATION, DÉLAI, NOTIFICATION DE LA DÉCISION, NOTIFICATION IRRÉGULIÈRE | 355 CPP (CH), 356 CPP (CH), 393 CPP (CH), 88 CPP (CH)